Functional and aesthetic integration in the design of the media poster - Yassin, Eman Taha; Salman, Asaad AbdulWahid (Al-Adab Journal, 2021)
Design is an essential work for every human being, because most of what a person does from works includes a measure of design, as design is one of these arts and the most applied to all activities aimed at organizing and creating things, and graphic design is one of the most important types of design that contains many works One of his most important works is the poster, and its types are the posters of films. The advertising poster for films is a work that transcends the local level to address the whole world, as a reduced and intense visual language that has created for itself a transformed path through time in line with the development of design thought and its technical changes, where its importance lies in being the link Between the producer and the consumer, it works through the design idea and good formality of the structural elements.